Schools betrayed: roots of failure in inner-city education - Neckerman, Kathryn M. (University of Chicago Press, 2007)
Urban decline -- Labor markets -- Communities and cultures -- Racial segregation and inequality -- Vocational education -- Remedial education -- Classroom dynamics -- Conclusion -- Appendix A. Quantitative evidence -- Appendix B. Some historical evidence about language styles and schooling